CARICA PAPAYA L. WITH SUTURE WOUND HEALING IN MICE EXPERIMENTAL ANIMALS - Istiqomah , Dani; Azizah, Nurul; Purwanti, Yanik; Rinata, Evi (UNIVERSITAS AIRLANGGA, 2023)
Background: Stitches are a condition in which skin tissue damage results from incisions or surgery and trauma. Carica Papaya Linn contains flavonoids which are efficacious as anti-inflammatory or antiseptic in inhibiting bacterial growth. Carica Papaya Linn is effective in repairing cells damaged by free radicals. The purpose of this study was to see the effectiveness of papaya leaf extract (Carica Papaya Linn) against stitches. Method: This research was quantitative research with a True Experimental design with the one group post-test method using the REEDA scale assessment. The population in this study were mice (Mus Musculus) which were divided into 5 groups, control group, nebacetin group, 5% test group, 10% test group and 15% test group. Research was conducted in the Lab. Medical Laboratory Technology at Muhammadiyah University of Sidoarjo and for making extracts from the Faculty of Mathematics and Natural Sciences, Surabaya State University. Data was collected and then the results were analysed using the One Way ANOVA statistical test. Result: The results of the statistical test showed a value of P = 0.000 in the 7th day group, which means there was a difference in each group of mice and the mean results showed the lowest result was 0.2 in the 15% extract which stated the best wound healing. Conclusion : The conclusion of the study was that there was an effect of giving papaya leaf extract (Carica Papaya L.) on wound healing in experimental mice.